UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI PENDAMPINGAN BELAJAR DARING PADA SISWA TERDAMPAK PANDEMI COVID-19 DI DESA MEKARJAYA KECAMATAN CIHAMPELAS KABUPATEN BANDUNG BARAT - Siti Purhasanah (Jurnal Al Maesarah, 2022)
Due to the long-lasting COVID-19 pandemic, the government has imposed rules for implementing long distance learning (online learning). This causes various problems for students, teachers and parents that need to be handled appropriately. The main problem that arises during online learning activities is the lack of student motivation. One of the efforts that can be done to overcome this problem is the assistance of students during the learning process. This assistance is carried out by helping the students to do school assignments, adding learning materials, guidance and counseling, and improving communications between parents and teachers.